Impaired Expression of Prostaglandin E2 (PGE2) Synthesis and Degradation Enzymes during Differentiation of Immortalized Urothelial Cells from Patients with Interstitial Cystitis/Painful Bladder Syndrome - Marentette, John O.; Hurst, Robert E.; McHowat, Jane (PLOS ONE, 2015)
Purpose The differentiated superficial cells of the urothelium restrict urine flow into the bladder wall. We have demonstrated that urothelial cells isolated from bladders of patients with interstitial cystitis/painful bladder syndrome (IC/PBS) fail to release PGE2 in response to tryptase. This study examines the expression of PGE2 synthesis and degradation enzymes in urothelial cells during differentiation. Materials and Methods We measured immunoprotein expression of cyclooxygenase-2 (COX-2), prostaglandin E2 synthase (PGES) and 15-hydroxyprostaglandin dehydrogenase (PGDH) in human urothelial cells and in immortalized urothelial cells isolated from the bladders of IC/PBS patients or normal subjects during stratification and differentiation produced by increased calcium and fetal bovine serum (Ca/FBS) in the culture medium for 1, 3 and 7 days. Results PGES immunoprotein expression increased during differentiation in normal and IC/PBS urothelial cells. COX-2 expression also increased in cells from normal patients following differentiation. Remarkably, no COX-2 expression was detectable in urothelial cells isolated from 3 out of 4 IC/PBS patients. PGDH immunoprotein expression decreased in normal cells after 1 and 3 days of Ca/FBS addition, but returned to normal after 7 days. PGDH expression was unchanged during differentiation at 1 and 3 days, but was more than 2-fold higher at 7 days compared to day 0 in the IC/PBS cells. Urothelial cells isolated from IC/PBS patients demonstrated no PGE2 release in response to tryptase under any of the experimental conditions studied. Conclusions Taken together, our results indicate that PGE2 release is compromised during stratification and differentiation in IC/PBS urothelium and may contribute to impaired barrier function.